Patient safety factors in children dying in a paediatric intensive care unit (PICU): a case notes review study. Issue 10 (19th May 2011) - Monroe, Kim; Wang, Deli; Vincent, Charles; Woloshynowych, Maria; Neale, Graham; Inwald, David P
Abstract : Objective: To identify patient safety factors in pre-hospital and hospital management of critically ill children dying in a paediatric intensive care unit (PICU). Design: Retrospective case notes review. Setting: Single tertiary regional PICU in London. Participants: 47 patients (7%) who died from a total of 679 children admitted during 2007 and 2008. Median age was 1.1 years and median predicted mortality from the Paediatric Index of Mortality 2 score was 39%. Main outcome measures: Adverse events contributing to death (AEds) and critical incidents (CIs). AEd was defined as an unintended injury or complication caused by health care management, contributing to death. CI was defined as an undesirable event in healthcare management, which could have led to harm or did lead to harm of the patient but did not contribute to the patient's death. Results: 22 AEds occurred in 17 of 47 (36%) cases. Two AEds occurred in primary care, 20 in pre-PICU hospital care, and none in PICU. AEds were mainly problems in diagnosis and management of critical illness. 37 CIs occurred in 28 of 47 (60%) cases. Two CIs occurred prior to hospital admission, 17 occurred in pre-PICU hospital care, 1 during inter-hospital transport and 17 in PICU. CIs were predominantly medical management and procedure related. Individual, team and organisational factors caused the majority of AEds and CIs. Conclusion: Adverse events in pre-PICU hospital care were common in children who subsequently died in PICU. CIs occurred throughout the patient journey. Interventional studies of healthcare organisation and delivery are necessary to identify appropriate strategies to improve patient safety.